2009
DOI: 10.1002/anie.200902468
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Determined Redox Potentials of Individual (n,m) Single‐Walled Carbon Nanotubes

Abstract: Ever since the discovery of carbon nanotubes (CNTs), many groups have endeavored to understand the fundamental properties of the CNTs. The redox properties (i.e. electronic densities, the Fermi levels, redox potentials) of single-walled carbon nanotubes (SWNTs) are related to the structures of SWNTs that have a specified diameter and chirality angle uniquely related to a pair of integers (n,m); the so-called chiral indices. [1,2] Many attempts have been made to determine the electronic properties of SWNTs usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
158
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 160 publications
(169 citation statements)
references
References 29 publications
10
158
1
Order By: Relevance
“…As shown in Fig. 4h, sem-SWNTs with (n,m) ¼ (6,5), (7,5), (7,6), (8,3), (8,4), (8,6), (8,7), (9,4), (9,5), (9,7), (10,2), (10,3), (10,5), (10,6), (11,3), (11,4), (11,6) and (12,2) were found to exist in the solution. In order to evaluate the extraction efficiency for each (n,m) chirality of the tubes, we calculated the relative contents of each SWNT based on the calibrated PL intensity using the method reported by Oyama et al 57 The calibrated contents of the SWNT species deduced from the PL mapping are shown in Supplementary Table 1, in which SWNTs with (n,m) ¼ (7,6), (8,6), (9,4) and (10,2) were enriched for the sample using CP-Zn.…”
Section: Synthesis Of Cp-mmentioning
confidence: 89%
See 1 more Smart Citation
“…As shown in Fig. 4h, sem-SWNTs with (n,m) ¼ (6,5), (7,5), (7,6), (8,3), (8,4), (8,6), (8,7), (9,4), (9,5), (9,7), (10,2), (10,3), (10,5), (10,6), (11,3), (11,4), (11,6) and (12,2) were found to exist in the solution. In order to evaluate the extraction efficiency for each (n,m) chirality of the tubes, we calculated the relative contents of each SWNT based on the calibrated PL intensity using the method reported by Oyama et al 57 The calibrated contents of the SWNT species deduced from the PL mapping are shown in Supplementary Table 1, in which SWNTs with (n,m) ¼ (7,6), (8,6), (9,4) and (10,2) were enriched for the sample using CP-Zn.…”
Section: Synthesis Of Cp-mmentioning
confidence: 89%
“…Not only their structural characteristics, but also opto-electronic properties derived from their diameters and chiral indices, denoted as (n,m)SWNTs, are important for a deep understanding of their fundamental intrinsic properties [1][2][3][4][5][6][7][8][9][10] . Highly purified semiconducting SWNTs (sem-SWNTs) not containing metallic SWNTs (met-SWNTs) are specifically required for electronic devices, such as field-effect transistors [11][12][13][14] and photovoltaic applications 15,16 because the met-SWNTs decrease and reduce the efficiency of their associated devices 17,18 .…”
mentioning
confidence: 99%
“…The PL signals from the SWNTs are originated from the exciton (recombination of electronhole pairs at the band gaps) of the isolated SWNTs, which is well-known in the carbon nanotube science. We fabricated a transparent indium tin oxide (ITO) electrode modified with a film of carboxymethylcellulose sodium salt (CMC)/poly(diallyldimethylammonium chloride) [30]. From the near-IR PL spectrum of the film (Fig.…”
Section: Pl Spectroelectrochemistry For Redox Potential Determinamentioning
confidence: 99%
“…Based on the results of the PL imaging and single SWNT PL spectroscopy, the stepwise quenching behavior of the PL from a single (7,5)-SWNT was detected as the outer-applied potentials increased. The Nernst equation analysis of the obtained potential-dependent PL plots provided the oxidation and reduction potentials of the (7,5) tube as 0.41 V and -0.38 V vs. Ag/AgCl, respectively, which shift from those of the bulk (7,5)-SWNTs (oxidation: 0.54 V and reduction: -0.47 V [30]). We further observed a PL blueshift [61][62][63][64] and narrowing of the line width as the external-applied potential to the single SWNT increases.…”
Section: Electronic States Of Single Swntmentioning
confidence: 99%
“…is critical: for example, too many functional addends can cause the loss of (opto)electronic and mechanical properties, too few and there may be no benefit to nanocarbon solubility or compatibility with a polymer matrix. 21 The first nanotube redox potentials have been probed using spectroelectrochemical methods, [22][23][24] and the redox potentials of reactants in aqueous systems are well studied. However, the exact potential of charged nanocarbon polyelectrolytes and redox potentials of reactants in anhydrous, aprotic solvents are not well known.…”
Section: Introductionmentioning
confidence: 99%